Factors influencing antibacterial activity of chitosan against Aeromonas hydrophila and Staphylococcus aureus (International Current Pharmaceutical Journal, 2016)
In this study, the effect of the incubation time, incubation temperature, pH, metal and sodium ions on the antibacterial activity of chitosan against food borne spoilage bacteria focused. Aeromonas hydrophila and Staphylococcus aureus were used as two food borne bacteria. Acetic acid was used dissolving of chitosan. Results showed that chitosan solution at 5 mg/mL significantly inhibited the growth of A. hydrophila and S. aureus in presence of time, pH and metal ions (p 0.01). Chitosan activity increased with increasing incubation time. The influence of below pH 6 on the antibacterial activity of chitosan was significantly influenced (p